Masculinity in Laura Dave’s The Last Thing He Told Me - Aufila, Sis; Andayani, Ambar (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
Abstract. This research is entitled "Masculinity in Laura Dave's The Last Thing He Told Me." The purpose of this study is to analyze the reflection and identify the types of masculinity presented in the story. This research uses a qualitative method and a sociological approach. This research aims to understand the reflections and types of masculinity experienced by the characters in the story. The theory used is Connell's theory of gender relations and masculinity to analyze how masculinity is portrayed in the story. The results show that masculinity is reflected in Hannah and Owen. The types of masculinity identified Hegemony, Subordinate, Complicity, and Marginalized. Hannah's character experiences problems, such as searching Owen's missing whereabouts, which makes her masculinity emerge. Likewise, Owen's character faces problems that prompt him to leave and protect his family. Moreover, this study shows that masculinity is not only associated with biological males, but can also be represented by female characters, challenging gender traditions. Hannah adopts male traits such as leadership, independence and emotional fortitude, demonstrating the fluidity of masculinity beyond gender boundaries. This study, by using Connell's framework, provides a deeper understanding of the complexities of masculinity in literature. Ultimately, the findings contribute to broader discussions about gender roles and how masculinity evolves in modern society.